Transferrin Insufficiency and Iron Overload in Follicular Fluid Contribute to Oocyte Dysmaturity in Infertile Women With Advanced Endometriosis - Li, Anji; Ni, Zhexin; Zhang, Jie; Cai, Zailong; Kuang, Yanping; Yu, Chaoqin (Frontiers in Endocrinology, 2020)
Purpose: To screen out specific protein with different concentration in follicular fluid from advanced endometriosis and determine its direct effect on mouse oocytes matured in vitro. Methods: FF samples were obtained from 25 patients (EMS group, n = 15; control group, n = 10) to screen the differential proteins by using iTRAQ Labeling and 2D LC-MS. Transferrin (TRF) in was found significantly decreased in EMS group, which was verified using ELISA in enlarged FF samples (EMS group, n = 31; control group, n = 27). The contents of ferric ion in FFs were detected by ELISA and TRF saturations were calculated in two groups. Germinal vesicle (GV) oocytes of mouse were maturated in vitro interfered with the FFs in five groups, whose concentrations of TRF were modulated, and maturation in vitro rates were compared among groups. Results: The reduced concentration of TRF with three analogs and increased concentration of ferric ion were found in the FF of the EMS group (p < 0.05). The numerical values of TSAT was 54.8% in EMS group, indicating iron overload in the FF. The EMS-FF showed significantly decreased maturation in vitro rate (p < 0.05) of mouse oocytes, which was improved with the supplementation of TRF, compared with the control-FF. The effect was blocked by the TRF antibody (p < 0.05). Conclusions: Being aware of the relatively small sample size, our results possibly suggest that TRF insufficiency and iron overload in FF from advanced EMS contribute to oocytes dysmaturity, which may be a cause of EMS-related infertility.